Vibrational properties of fractionally charged molecules and their relevance for molecular electronics and electrochemistry - Bâldea, Ioan (Chemical physics, 2017)
Important insight into the charge transfer across interfaces can be gained in situations wherein, for given adsorbate and substrate species, the (fractional) charge state of the adsorbed molecules can be varied in a controlled way. Applied biases can continuously tune the charge of molecules embedded in nanojunctions and/or in electrochemical setups but information on the fractional charges of the corresponding partial oxidized/reduced states cannot be directly accessed in experiments. Here, we present theoretical results revealing that information on the fractional molecular charge can be obtained by monitoring molecular vibrational properties, which can be measured by means of surface enhanced Raman spectroscopy (SERS). To this aim, we performed DFT calculations for the benchmark 1,4-benzenedithiol molecule. The changes in the vibrational frequencies are considerably larger than those recently measured in combined transport-SERS studies on molecular junctions based on fullerene. We believe that this theoretical result is an encouraging message to experimentalists.
Available online 26 August 2016
Gesehen am 03.08.2018